تعزيز الأمن السيبراني في الجزائر الجهود القانونية، العلمية والعملية - قيطة، فاطمة الزهراء; صالحي، دليلة (University Of Eloued جامعة الوادي, 2024)
إنّ كل المؤشرات تنبأ بخطر داهم في مجال الجريمة الإلكترونية، فالاختراقات الإلكترونية والهجمات السيبرانية بمختلف أشكالها ستكون في المستقبل أخطر على الجانب المعلوماتي والجانب المادي، ولها تأثير مدمّر على البُنى التحتية يفوق الأضرار الناجمة عن الكوارث الطبيعية، خاصةً مع التزايد السريع للأجهزة المتصلة بالشبكة العنكبوتية، ونمو المعاملات الإلكترونية والتطبيقات المتعلقة بها في مختلف المجالات. وتأسيسا على ذلك، بات من الأهمية بمكان تبنّي الدول والحكومات، خاصة العربية، إستراتيجيات تعززّ بها أمنها السيبراني، وإنشاء وحدات أو هيئات مختصة بحماية البنى التحتية من المخاطر الإلكترونية، وعلى رأس ذلك الاستثمار في البحث العلمي، وزيادة الوعي بهذا المجال بما يعزّز مستوى الأمن ومواكبة التكنولوجيا والتقنيات الحديثة التي من شأنها أن تجعل الأنظمة الإلكترونية أكثر أمنا، دون إغفال جانب التشريعات القانونية التي من شأنها مواجهة تحديات الأمن السيبراني بشكل أكثر صرامة وفاعلية. والجزائر كغيرها من الدول تسعى إلى تعزيز أمنها السيبراني، في مواجهة مخاطر الرقمنة التي أضحت تهدد الأمن الوطني، خاصة في ظل التوجه نحو الحكومة الإلكترونية. وهنا تسعى هذه الورقة البحثية إلى معرفة خطوات وبرامج الاستراتيجية الجزائرية في مجال تدعيم الأمن السيبراني. Summary Cybercrime will not disappear soon, as cyber-intrusions and cyber-attacks of all kinds will be worse and more costly in the future, and have a more devastating impact on infrastructure than damage caused by natural disasters, especially with the rapid increase in devices connected to the Internet, and the growth of electronic transactions and applications related to them in various fields. Based on this, it has become of great importance for countries and governments, especially Arab countries, to adopt strategies to enhance their cyber security, and to establish units or bodies specialized in protecting infrastructure from electronic risks, on top of that investing in scientific research and raising awareness in this field in order to enhance the level of security and keep pace with Technology and modern technologies that would make electronic systems more secure without neglecting the aspect of legal legislation that would confront cyber- security challenges in a more stringent and effective manner. Algeria, like other countries, seeks to enhance its cyber security in the face of the risks of digitization that have become a threat to national security, especially in light of the trend towards e-government. Here, this research paper seeks to know the steps and programs of the Algerian strategy in the field of strengthening cyber- security.
مداخلة
Keywords: الجريمة السيبرانية; الأمن السيبراني; التنظيم القانوني; الاستراتيجية; cyber crime; cyber security; legal regulation; strategy